PENGARUH MEDIA BAHAN ORGANIK DAN DOSIS TANAH LATOSOL PADA PASIR ERUPSI MERAPI TERHADAP HASIL BAWANG MERAH (Allium cepa fa. ascolanicum) - Cita Puspitaning Utami; Rahayu Sarwitri; Hadi Rianto (Universitas Tidar, 2017)
A research on the influence of organic material media and latosol soil dose of Merapi’s eruption sand on onion (Allium cepa fa. ascolanicum) was held in October 5th to December 7th 2015 in Taman Kyai Langgeng, Department of Agriculture and Fisheries of Magelang. The aims of research is to determine the highest yield of onion on organic material kinds and latosol soil dose. The method used was factorial experiment (4 x 3) arranged in a complete randomized block design with three replications. The first factor was the treatment of organic matter cocopeat, husk, and peat. The second factor was the latosol soil dose 0, 2.5 , 5 and 7.5 ton / ha. Variance test by using LSD on the first factor and orthogonal polynomials test for the second factor. The results showed that the cocopeat media 20 ton/ha + mikoriza 10g/ the planting hole gave the highest yield on the fresh weight of roots and weight of dry roots parameters. Husk media gave the highest yield on the tuber number parameters, fresh weight of bulbs and weight dry of bulbs. Latosol soil dose did not give affect to the yield of onion crop. Combination treatment between kinds of soil organic matter with a dose equal latosol responded to the onion crop yield.